2014
DOI: 10.2166/wst.2014.468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reverse osmosis membrane fouling characteristics in full-scale leachate treatment systems with chemical coagulation and microfiltration pre-treatments

Abstract: Fouling characteristics of reverse osmosis (RO) membrane with chemical coagulation and microfiltration (MF) pre-treatment were investigated at full-scale leachate treatment systems. In chemical coagulation pre-treatment, solid separation from stabilized leachate was performed by ferric chloride coagulation followed by sand filtration. Meanwhile, MF pre-treatment and the RO system utilized direct filtration using a 0.03 µm membrane without chemical addition. MF pre-treatment yielded better pollutant removals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, it is very important to research a type of concentrator with low energy consumption, low cost and free from pollution. In recent years, many kinds of membrane technologies such as microfiltration (MF), ultrafiltration, nanofiltration (NF) and reverse osmosis (RO) have been used to treat high salinity leachate wastewater [ 8 , 9 ]. Studies have shown that RO and NF were capable of concentrating seawater and brines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to research a type of concentrator with low energy consumption, low cost and free from pollution. In recent years, many kinds of membrane technologies such as microfiltration (MF), ultrafiltration, nanofiltration (NF) and reverse osmosis (RO) have been used to treat high salinity leachate wastewater [ 8 , 9 ]. Studies have shown that RO and NF were capable of concentrating seawater and brines [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Additionally, leachate treatment is inuenced by the production effluent and the quality of RO and NF technology. 8 Membrane technology can effectively decrease the COD, BOD 5 , and total nitrogen content; [9][10][11] however, it is constrained by the limited service life of RO and NF membranes and by the increasing treatment expense due to membrane pollution by extremely high concentrations of humic acid and fulvic acid. 12 Coagulation is widely applied to the pretreatment of concentrated leachate because of its convenient operation and its low cost; however, it is not very effective in removing organics in concentrated leachate.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the two approaches was proven to be able to effectively remove organics and reduce membrane fouling (Huang, He et al, 2015). Rukapan et al (2015) indicated that chemical coagulation had a higher performance than microfiltration as a pretreatment technology in reducing the fouling of reverse osmosis membrane. Nevertheless, many parameters in chemical coagulation would affect membrane fouling.…”
Section: Coagulation/flocculationmentioning
confidence: 99%